Subscapularis Tendon Repair Improves Functional Internal Rotation after Onlay Design Reverse Shoulder Arthroplasty - Felipe Lacerda; Alexandre Lädermann; Mahmoud Faisal Adam; Angélique Delarue; Céline Daniel; Philippe Collin (The Hive)
Background: A major challenge of the reverse shoulder arthroplasty (RSA) is to restore postoperative range of motion, especially internal and external rotation. Attempting to address this issue, several modifications to the prosthesis design have been made.